SOME OBSERVATIONS ON THE PRODUCTION CAPACITY OF NATIVE MOUNTAIN SHEEP - ΚΑΤΣΑΟΥΝΗΣ, Ν.; ΖΥΓΟΓΙΑΝΝΗΣ, Δ. (Journal of the Hellenic Veterinary Medical Society, 1974)
The authors studied the meat performance of lambs produced in Greece from the mountain type native sheep as well as the ability of ewes to suckle two lambs together. It was observed that the milk yield was low, and the ewes could not suckle satisfactory twin lambs. On the other hand the meat yield of the lambs could not be increased on the basis of the nutrition improvement only, but an improvement of the genetic material by hybridization was necessary.